In-Depth Characterization of Plant Growth Promotion Potentials of Selected Alkanes-Degrading Plant Growth-Promoting Bacterial Isolates - Alotaibi, Fahad; St-Arnaud, Marc; Hijri, Mohamed (Frontiers in Microbiology, 2022)
The use of plant-growth-promoting rhizobacteria (PGPR) as a bioremediation enhancer in plant-assisted phytoremediation requires several steps, consisting of the screening, selection and characterization of isolates. A subset of 50 bacterial isolates representing a wide phylogenetic range were selected from 438 morphologically different bacteria that were originally isolated from the petroleum hydrocarbon (PHC)-polluted site of a former petrochemical plant. Selected candidate bacteria were screened using six conventional PGP traits, complemented with the genetic characterization of genes involved in alkane degradation, as well as other pertinent functions. Finally, the bacterial isolates were subjected to PGP tests using a gnotobiotic approach under normal and stressed conditions. Our results indicated that 35 bacterial isolates possessed at least 4 PGP traits. Twenty-nine isolates ( were able to utilize n-hexadecane as a sole carbon source, whereas 43 isolates were able to utilize diesel as the sole carbon source. The presence of catabolic genes related to hydrocarbon degradation was assessed using endpoint PCR, with the alkane monooxygenase (alkB) gene found in 34 isolates, the cytochrome P450 hydroxylase (CYP153) gene found in 24 isolates and the naphthalene dioxygenase (nah1) gene found to be present in 33 isolates. Thirty-six strains promoted canola root elongation in the growth pouch assay. After several rounds of screening, seven bacterial candidates (individually or combined in a consortium) were tested for canola root and shoot growth promotion in substrates amended by different concentrations of n-hexadecane (0%, 1%, 2%, 3%) under gnotobiotic conditions. Our results showed that Nocardia sp., Pseudomonas plecoglossicida, Stenotrophomonas pavanii and Gordonia amicalis significantly increased the root length of canola grown in 3% n-hexadecane compared with the control treatment, whereas Nocardia sp. and Bacillus megaterium significantly increased shoot length compared to control treatment at the same concentration of n-hexadecane. The consortium had a significant enhancement effect on root length compared to all isolates inoculated individually or to the control. This study demonstrates that the combination of PGPR traits and the PHC potential of bacteria can result in an enhanced beneficial effect in phytoremediation management, which could lead to the development of innovative bacterial inoculants for plants to remediate PHC-contaminated soils.